Anthropometric Study of the Relationship Between Tibia Length and Height Ethnic Papuans - Frollivia Adolina Meiselin Iwanggin; Indra Harianto Rante (RSUP Dr. Kariadi, 2024)
BACKGROUND : Height is an important main characteristic in the forensic anthropological identification process to determine the identity of a person. Estimating height based on the length of long bones such as the tibia, fibula, ulna, and humerus is one method that is widely used because it has a good correlation. This study was conducted to determine the relationship between tibia bone length and height in students of the Medical Education Study Program, Faculty of Medicine, Cenderawasih University who are indigenous Papuan. METHOD : This study applied correlative analytic method with a cross sectional approach. The research sample was students of the Medical Education Study Program at Cenderawasih University in 2020-2023. The tibia bone length was measured using a metline and height was measured using a microtoise directly on the research subject. Data were analysed with Pearson test. RESULT : Fifty-five subjects (25 males, 30 females), and found male height of 161.060 cm, a female height of 153.000 male tibia bone length of 26.620 cm, and a female of 34.170 cm. CONCLUSION : There was a relationship between tibia length and height with the results of the Pearson test obtained P value = <0.001